META-ANALYSIS EFFECTIVENESS OF PROBLEM-BASED LEARNING MODEL IN SOCIAL SCIENCES - Lubna Lubna (Jurnal Tatsqif, 2020)
This research is intended to analyze the effectiveness of problem-based learning in social sciences settings. The study employed a quantitative approach using a meta-analysis method which is defined as the analysis of the same topic existing literature. This study referenced 4 out of 9 representative journals and was determined as the analysis unit. Subsequently, it is decided to make six sub-study out of four analysis unit. Glass’ effect size equation is employed as the data analysis. This study revealed, (1) the overall effect of the problem-based method on the students’ learning achievement standard deviation was 0,795, (2) the utilization of problem-based method showed significant result on the highly motivated and gifted students; (3) this learning method is relevant to all educational stage.